A Dental Response to the COVID-19 Pandemic—Safer Aerosol-Free Emergent (SAFER) Dentistry - Benzian, Habib; Niederman, Richard (Frontiers in Medicine, 2020)
Dental services are significantly impacted by the COVID-19 pandemic. Almost all dental procedures carry a high infection risk for providers and patients due to the spread of aerosols. As a consequence, public health agencies and professional associations have issued guidelines for enhanced infection control and personal protection equipment and have also limited care to urgent or emergency services. However, there is no dental service concept for pandemic disaster preparedness or response that might be applied. Moreover, pathways to dental care provision in a post-pandemic future with persisting risks are needed. We propose Safer Aerosol-Free Emergent Dentistry (SAFER Dentistry) as one approach to dental services during and emerging from the pandemic. The concept's starting point is the identification of the most common patient needs. The next step is to replace common treatments addressing the most frequent needs with alternative interventions involving a lower infection risk because they do not generate aerosols. SAFER Dentistry is innovative, avoids risk, and responds to the requirements of a pandemic and post-pandemic emergency where the risk of airborne disease transmission remains high. SAFER Dentistry thereby ensures continuity of dental services while protecting providers and patients from infectious pathogens. Moreover, SAFER Dentistry allows dental service providers to remain operational and generate income even under pandemic conditions. Potential implementation and policy options for SAFER Dentistry include universal availability without co-payments by patients and a uniform bundled payment scheme for providers to simplify budgeting, reimbursement, and administration during a pandemic. Adaptations and adjustments of the concept are possible and encouraged as long as the principle of avoiding aerosol-generating procedures is maintained.